IMPLEMENTASI PENYEDERHANAAN FUNGSI BOOLE DENGAN METODE QUINE McCLUSKEY - Alfatah Hidayat; Siti Rahmah Nurshiami; Mashuri Mashuri (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2021)
Quine McCluskey method is one method that can be used to simplify the Boolean function. The Quine McCluskey method has several advantages including having simpler, more systematic steps than other methods and it is easier to simplify the Boolean function with a large number of variables. This study discusses the design of a Boolean function simplification program for the Quine McCluskey method using Visual Basic 6.0. The resulting program can simplify the Boolean function with many variables less than equal to 26 variables and able to simplify the Boolean function in the form of Sum of Product (SOP), Product of Sum (POS), and don't care.